2006
DOI: 10.1016/j.cub.2006.06.027
|View full text |Cite
|
Sign up to set email alerts
|

A Command Chemical Triggers an Innate Behavior by Sequential Activation of Multiple Peptidergic Ensembles

Abstract: Our findings offer novel insights into how a command chemical orchestrates an innate behavior by stepwise recruitment of central peptidergic ensembles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
326
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 217 publications
(349 citation statements)
references
References 53 publications
22
326
0
1
Order By: Relevance
“…In related work, we have shown that ensembles of neurons in D. melanogaster homologous to those in M. sexta (EH-containing VM neurons, CCAP͞MIPs-containing IN704 neurons, and CCAP͞ bursicon-containing NS27 neurons) become active at the onset of successive behavioral subunits (15). Taken together, these findings indicate that sequential recruitment of peptidergic ensembles elicits components of an innate behavior in stepwise fashion.…”
Section: Recruitment Of Innate Behaviors By Peptidergic Networkmentioning
confidence: 65%
“…In related work, we have shown that ensembles of neurons in D. melanogaster homologous to those in M. sexta (EH-containing VM neurons, CCAP͞MIPs-containing IN704 neurons, and CCAP͞ bursicon-containing NS27 neurons) become active at the onset of successive behavioral subunits (15). Taken together, these findings indicate that sequential recruitment of peptidergic ensembles elicits components of an innate behavior in stepwise fashion.…”
Section: Recruitment Of Innate Behaviors By Peptidergic Networkmentioning
confidence: 65%
“…3). These mutant SP and MIP1 peptides (SP [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] W23A,W32A , MIP1 W2A,W9A ) were completely inactive even in 10 μM concentration (Table 1), suggesting that these residues, and by inference the turn conformations, are critical for SPR activation. Furthermore, an MIP mutant (DmMIP1 3-8A ) carrying Ala-replacements in all residues except the conserved Trp residues retained a strong SPR agonist activity (Table 1).…”
mentioning
confidence: 99%
“…59,60,[67][68][69][70] To truly understand the ecdysis behavior we have to examine the raison d'être of the molting process. Insects and crustaceans have a rigid exoskeleton and therefore to accommodate growth they have to periodically shed the exoskeleton and replace it with a new one.…”
Section: Ecdysis Motor Behavior Controlling Peptides: Ptth Eh Pethmentioning
confidence: 99%
“…The new cuticle is elaborated, sclerotized and hardened with the help of another neurohormone, bursicon (a 173 amino acid protein belonging to the cystine knot family of growth factors), which is coexpressed with CCAP in the bilateral ventral neurons in the central nervous system of Drosophila. 59,[67][68][69][70]73) The ecdysis cascade begins with the ventro-median cells (VM cells) secreting the eclosion hormone (EH) in the presence of 20E, which is stored in the proctodeal nerves (proct. nerve) which serves as the neurohemal organ and is released in the absence of 20E (Fig.…”
Section: Ecdysis Motor Behavior Controlling Peptides: Ptth Eh Pethmentioning
confidence: 99%